Impact of milk production and important management factors on the process of dry-off in lactating dairy cows - R.T. Dingwell; K.E. Leslie; J.M. Sargeant; Y.H. Schukken (Kansas Agricultural Experiment Station Research Reports, 2001)
A study of 250 cows located in Canada and the United States revealed the rate of new mammary infections was 9.9% during the dry period. Average milk production on the day prior to dry-off was 13.2 ± 7.2 kg. The odds of a cow developing a new infection was three times greater if the cow was producing more than 5 kg of milk. After 6 weeks of the dry period, 25% of the teats still remained open. This research will serve as the foundation to investigate and implement management strategies prior to dry-off that might improve the overall udder health of dairy cows.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Dry-off; Mastitis; Milk production